2017
DOI: 10.3855/jidc.8421
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and multilocus genotyping of Giardia duodenalis in pets and zoo animals in Shanghai, China

Abstract: Introduction: High prevalence of Giardia infections occurs in humans and animals, partly because of the increasing numbers of pets. We determined the presence and genotypes of G. duodenalis in pets and zoo animals. Methodology: A total of 84 specimens were collected from dogs and cats from a pet hospital, and 54 specimens from a zoo, which included deer, tigers, yaks, and others. All the specimens were examined by microscopy and by polymerase chain reaction (PCR) amplification and subsequent sequencing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…In Niaoning Province, the infection rate of G. duodenalis in farm dogs was 13.2% [ 24 ]. In Shanghai, Hualiu et al [ 25 ] reported that G. duodenalis was found in 26.67 and 9.26% of samples from pets and zoo animals, respectively. The infection rate of G. duodenalis in pet chinchillas was 27.1% in four different cities in China [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Niaoning Province, the infection rate of G. duodenalis in farm dogs was 13.2% [ 24 ]. In Shanghai, Hualiu et al [ 25 ] reported that G. duodenalis was found in 26.67 and 9.26% of samples from pets and zoo animals, respectively. The infection rate of G. duodenalis in pet chinchillas was 27.1% in four different cities in China [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Giardia have been reported in captive animals such as non-human primates (NHPs) and wild birds worldwide, and zoonotic assemblages A and B of G. duodenalis have been found, which indicates the importance of the study of G. duodenalis in wild animals (Oates et al ., 2012; Reboredo et al ., 2015; Mynářová et al ., 2016). Animal husbandry is commonplace in China and the role of livestock and pets in the transmission of Giardia has been studied extensively (Liu et al ., 2014, 2017; Qi et al ., 2016). However, very little information is available on the prevalence of G. duodenalis in the captive animals in China, and the assemblage distribution and the multilocus genotyping (MLG) of G. duodenalis remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…As stated, isolates of G. duodenalis assemblage F were also identified in one chinese leopard (Panthera pardus fontanierii) [= P. p. japonensis], two siberian tigers (Panthera tigris altaica) and mix assemblages D/F in a leopard (Panthera sp.) in Chinese zoo (Li et al 2017, Liu et al 2017.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the previous data concerning G. duodenalis identification in felids derived from research on domestic or stray cats (Felis catus) (Cacciò et al 2008, Cacciò et al 2010de Lucio et al, 2017;Gil et al, 2017;Kváč et al 2017;Li et al 2017;Lebbad et al 2010;Suzuki et al 2011;Read et al 2004;Pallant et al 2015;Palmer et al 2008;Jaros et al 2011;McDowall et al 2011;Sotiriadou et al 2013;Souza et al 2007). In addition to reports from individual captive wildcats (Beck et al 2011, Li et al 2017, Liu et al 2017, only one study has used molecular-based techniques and sequence analysis to identify G. duodenalis assemblages in feacal material from free-living wild felids (Oates et al 2012). Given the lack of molecular genotyping of Giardia isolates from European wildcats (Felis s. silvestris), the aims of the present study were (i) to use loop-mediated isothermal amplification (LAMP) for rapid detection of G. duodenalis zoonotic assemblages, (ii) and to genotype Giardia isolates recovered from wild wildcats by polymerase chain reaction (PCR).…”
Section: Introductionmentioning
confidence: 99%